(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2016)
Global warming has been considered due to carbon dioxide emission and efforts are diverted to reduce the carbon dioxide emission. In this paper some different approach has been highlighted. In the Sun hydrogen fusion reaction has been going on for last 5 billion years. This fusion reaction has been yielding helium gas and it is believed that hydrogen gas is almost consumed and helium fusion has started. This fusion produces almost 100 times more heat causing the surface of the Sun getting more temperature. Due this increase in the Suns temperature, temperature on the earth is also increased which we experience as global warming. This paper discusses this view in depth.